THEORETICAL ASPECTS OF TRAINING AND PLAYING ACTIVITIES OF HANDBALL PLAYERS - Назаревич, Володимир; Вожжов, Ілля (SWorldJournal, 2023)
It is possible to improve the physical training of an athlete with the help of general and special exercises. Handball perfectly develops accuracy, reaction speed and the ability to work in a team, as well as strengthens leg muscles.With the help of gen